Esterase and phosphoglucomutase polymorphism in the rambutan fruit borer, Conopomorpha cramerella (Snellen) - Ahmad, Halmy; Tan, Soon Guan; Muhamad, Rita; Gan, Yik Yuen (Malaysian Plant Protection Society, 1987)
Adult Conopomorpha cramerella collected from rambutan fruit from Serdang, Malaysia were subjected to polyacrylamide gel electrophoresis. Esterase-1, esterase-2 and phosphoglucomutase were found to be polymorphic while NADH dehydrogenase was monophormic. The two esterases and phosphoglucomutase are potentially useful biochemical markers for population genetic studies as each locus had three common alleles in the population analysed.